The Benefits of Obesity Medicine Certification. Issue 2 (March 2019) - Alexander, Lydia
With the majority of patients seen by primary care practitioners suffering from overweight or obesity, an additional certification in obesity medicine provides the critical tools and skillset to expertly address the many chronic health conditions predicated by unhealthy adiposity and excess weight.